JAMINAN KEPASTIAN PERLINDUNGAN HUKUM TERHADAP DRIVER OJEK ONLINE: STUDI KASUS PEMBERITAAN MEDIA NASIONAL DEMONSTRASI AKBAR DRIVER GRAB MEI 2025 - Syahruni Aryanti; Agus Satory (JOURNAL OF LAW AND NATION, 2025)
This study analyzes the guarantee of legal certainty and protection for online motorcycle taxi (ojol) drivers in Indonesia through a case study of national media coverage regarding the Mass Demonstration of Grab Drivers in May 2025. A qualitative content analysis method was applied to 58 news articles from Kompas.com, Detik.com, Tempo.co, CNNIndonesia.com, Liputan6.com, Tirto.id, and Kontan.co.id published throughout January-May 2025. Findings reveal that media coverage predominantly reflects the absence of adequate legal certainty for drivers, particularly concerning unfair wages, non-transparent fare algorithms, unilateral termination mechanisms, and weak bargaining power in policy negotiations. Media played a crucial role in elevating this issue to public discourse, prompting government response. However, analysis indicates that existing legal frameworks—especially Law No. 11 of 2020 on Job Creation and its derivative regulations—remain ineffective in ensuring essential protections for gig economy workers. The study concludes that progressive policy reforms are imperative to establish equitable legal certainty and social security guarantees for ojol drivers.